Clinical features of pagetoid spread: Analysis of perianal lesions associated with anal canal adenocarcinoma and perianal primary extramammary Paget disease. Issue 4 (16th February 2023) - Kosano, Megumi; Kiniwa, Yukiko; Mikoshiba, Asuka; Iwaya, Mai; Okuyama, Ryuhei
Abstract: Secondary extramammary Paget disease (s‐EMPD) represents anal canal and rectal, bladder, and gynecological cancers, which horizontally extend within the epidermis of the anal and vulvar skin. It is necessary to distinguish this condition from primary extramammary Paget disease (p‐EMPD), which occurs primarily in genital and perianal areas. This study aimed to investigate the clinical and histopathological features of these two conditions in the perianal skin and to identify useful features for differentiation. We retrospectively analyzed 16 patients who visited Shinshu University Hospital from 2009 to 2022 and presented with perianal skin lesions and suspected EMPD. Six patients had p‐EMPD and 10 had s‐EMPD derived from anal canal adenocarcinoma. Regarding clinical features, nine of 10 (90%) of the s‐EMPD cases had symmetric skin lesions, whereas all of the p‐EMPD cases had asymmetrical lesions ( p = 0.0004). Furthermore, assessment of symmetry around the anus showed that s‐EMPD had a significantly smaller coefficient of variation than p‐EMPD (0.35 and 0.62, respectively; p = 0.048), suggesting that s‐EMPD was more symmetric around the anus. The frequency of raised lesions, such as foci or nodules, was nine of 10 (90%) for s‐EMPD and one of six (16%) for p‐EMPD ( p = 0.003). Well‐defined tumor borders on the lateral margins were identified in s‐EMPD (5/10, 50%); however, they were not identified in p‐EMPD (0/6, 0%). The borders tended to be clearer in s‐EMPD; however, the difference was not significant ( p = 0.078). Based on these findings, we recommend consideration of s‐EMPD when anal skin lesions are symmetrical, well‐defined, or raised.